2021
DOI: 10.1158/1078-0432.ccr-20-3159
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Validation and Observer Performance Study of a Deep Learning Algorithm for Pathologic Diagnosis of Gastric Tumors in Endoscopic Biopsies

Abstract: Purpose: Gastric cancer remains the leading cause of cancer-related deaths in Northeast Asia. Population-based endoscopic screenings in the region have yielded successful results in early detection of gastric tumors. Endoscopic screening rates are continuously increasing, and there is a need for an automatic computerized diagnostic system to reduce the diagnostic burden. In this study, we developed an algorithm to classify gastric epithelial tumors automatically and assessed its performance i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Lastly, it can be used to develop an algorithm for rare cancers for which there does not exist a large number of histologic images, using datasets from more well-known cancer types that bear histologic resemblance. Previous DL algorithms in digital pathology developed models without considering morphological similarities or dissimilarities among cohorts [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . While several studies already demonstrated the morphological similarities using cross-cohort classification 22,25 and pan-cancer/tissue classification 18,23 , our work takes an additional step Sampled positive and negative patches of all cohorts are shown below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it can be used to develop an algorithm for rare cancers for which there does not exist a large number of histologic images, using datasets from more well-known cancer types that bear histologic resemblance. Previous DL algorithms in digital pathology developed models without considering morphological similarities or dissimilarities among cohorts [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . While several studies already demonstrated the morphological similarities using cross-cohort classification 22,25 and pan-cancer/tissue classification 18,23 , our work takes an additional step Sampled positive and negative patches of all cohorts are shown below.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, data-driven algorithms including deep learning (DL) have been devised to detect cancer using H&E morphology 2 . While a larger dataset size used to train DL algorithms directly translates to better performance, previous cancer detection models have been trained on cancer-specific datasets such as breast cancer 2-5 , skin cancer 6-8 , lung cancer 9 , bladder cancer 10 , prostate cancer 8,11,12 , stomach cancer [13][14][15] , colon cancer 14 and lymph node metastases 8,16,17 , with restricted capacity from limited data. Another approach is to develop a universal model with the hope that increasing the dataset size outweighs the drawbacks brought by introducing irrelevant information or features 18 .…”
mentioning
confidence: 99%
“…In recent years, AI has been used in the eld of pathologic image diagnosis, and many studies have shown promising results in detecting and diagnosing cancers in a variety of organs, including the stomach, breast, skin, prostate, brain, and lung [13,[22][23][24]. As for cervical cancer, with the advancement in the management of preinvasive lesions, the increasing diagnostic workload of cervical biopsy calls for the development of high-performance algorithms with high sensitivity and speci city.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al, trained a DL algorithm to identify gastric cancers in endoscopy biopsy specimens and showed that the system can increase time to diagnosis and may be potentially applied in countries with a lack of specialized pathologists [ 169 ]. Similarly, a recent multicentric study built a DL-based algorithm to aid in the diagnosis of gastric cancer and applied this using data from different scanners and different hospitals showing its generalization [ 170 ].…”
Section: Machine Learning—basic Concepts Specific Applications and Future Directions In Geamentioning
confidence: 99%